2021
DOI: 10.1177/2382120521991150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety and Depression Among Medical Students During the Covid-19 Pandemic: A Cross-Sectional Study

Abstract: Purpose: The Covid-19 pandemic is a public health emergency with both physical and mental health risks. Medical students have baseline elevated rates of anxiety, depression and burnout. As such, they may be especially susceptible to the psychological stresses of Covid-19. The current study aimed to evaluate the prevalence of anxiety and depression among United States medical students during the Covid-19 pandemic. Methods: A cross-sectional, survey-based study collected demographic data as well as the 7-item Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
164
6
16

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(213 citation statements)
references
References 15 publications
27
164
6
16
Order By: Relevance
“…Iran and the United Arab Emirates also showed greater burden amongst female students and students in clinical training years [18][19][20]. A social media study in the US suggests rates of anxiety and depression among medical students may have increased during the pandemic [21], but there has not yet been an attempt to use census sampling to estimate prevalence of anxiety or PTSD in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Iran and the United Arab Emirates also showed greater burden amongst female students and students in clinical training years [18][19][20]. A social media study in the US suggests rates of anxiety and depression among medical students may have increased during the pandemic [21], but there has not yet been an attempt to use census sampling to estimate prevalence of anxiety or PTSD in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Negative effects of the COVID-19 crisis on the mental health of non-medical university students have already been reported early on, 18 19 with more students experiencing higher rates of stress and perceived social isolation, 20 as well as a higher prevalence of anxiety and depression than in the pre-COVID-19 era. 21 Medical students, along with experiencing increased deterioration of their mental health in the pandemic, also expressed concerns about the pandemic disrupting their studies and not allowing them to adequately prepare for clinical practice. 22 It is without question that the COVID-19 pandemic affected both the preclinical and clinical aspects of medical education with very quick initial transitions into online and small group education formats.…”
Section: Introductionmentioning
confidence: 99%
“…11 Also, our result was similar to a study conducted among medical students in the United States which showed 30.6% anxiety. 12 In this study by Halperin et al, anxiety and depression was seen more among first year and second year medical students (pre-clinical) compared to third year and final year. 12 But in our study composite anxiety-depression category was higher among the final year medical students.…”
Section: Discussionmentioning
confidence: 63%